Evaluation of accuracy of ultrasonography in the diagnosis of zygomatic arch fractures - Mozhdeh Mehdizadeh; Moein Hoseini-Shirazi; Forouzan Farahbod (Isfahan University of Medical Sciences, 2011)
Introduction: In recent years, computed tomography (CT) scan has become an alternative to conventional radiography; however, the use of ultrasound in detecting zygomatic arch fractures has been rarely evaluated. The aim of this study was to evaluate accuracy of ultrasonography in the diagnosis of zygomatic arch fractures.Materials and methods: Fifteen patients (9 men and 6 women) with clinical signs of midfacial fractures, whose CT scan findings showed unilateral zygomatic arch fracture, were selected. All the patients underwent bilateral ultrasound examinations. All the sonographic techniques were carried out and interpreted by the same sonologist who was not aware of the CT results. Data were analyzed to determine sensitivity and specificity of ultrasonography in the diagnosis of zygomatic arch fractures.Results: Ultrasound assessed the fractured arches with a sensitivity of 100% (15 of 15 patients, with no false negatives) and the un-fractured arches with a specificity of 100% (no false positives).Conclusion: Based on the results of the present study ultrasound is a useful diagnostic tool for zygomatic arch fractures in initial investigations, and can help reduce the total number of diagnostic radiographic procedures and overall radiation exposure.Key words: Diagnosis, Fracture, Ultrasonography, Zygomatic arch.